Junior high school students’ onto-semiotic approach in solving AKM-oriented algebra numeracy problems based on VARK learning styles - Hidayat, Rifqi; Turmudi, Turmudi; Dahlan, Jarnawi Afgani; Nurlaelah, Elah (Universitas Jambi, Indonesia, 2026)
This qualitative phenomenological study examines how eighth-grade students with different VARK learning styles apply the onto-semiotic approach to solve AKM-oriented algebra problems. Using purposive sampling, data were collected through tests, questionnaires, interviews, and documentation, focusing on key mathematical objects: language, context, concepts, propositions, procedures, and arguments. The findings indicate that visual, auditory, and kinaesthetic learners demonstrate stronger abilities in linking contextual problems to mathematical models, interpreting symbols, identifying variables, and correctly applying substitution. They also construct meaningful algebraic propositions that align with the problem contexts. In contrast, read/write learners tend to rely on procedural and mechanical steps, often overlooking conceptual understanding and struggling to connect contextual information with symbolic representation. Consequently, although they may arrive at correct numerical solutions, their grasp of relationships between variables in linear equations remains limited.